2021
DOI: 10.1038/s41598-021-92365-y
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-wide scanner for large-area high-speed atomic force microscopy with megapixel resolution

Abstract: High-speed atomic force microscopy (HS-AFM) is a powerful tool for visualizing the dynamics of individual biomolecules. However, in single-molecule HS-AFM imaging applications, x,y-scanner ranges are typically restricted to a few hundred nanometers, preventing overview observation of larger molecular assemblies, such as 2-dimensional protein crystal growth or fibrillar aggregation. Previous advances in scanner design using mechanical amplification of the piezo-driven x,y-positioning system have extended the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…In the simulations that follow, the scanned image area containing the mobile component is subjected to raster scanning at either a slow, medium or fast scanning speed such that t SCAN ∈ (1,10,100) s. Interpreted through the lens of Eqn. 5 this implies that for a square image scan area of L=10 μm, and a typical AFM device setup with a tip size ϕ ∈ (10, 100) nm, the required AFM cantilever tip oscillation frequencies and tip lateral scan velocities will be in the respective ranges, f ∈ (100, 1×10 6 ) and υ x ∈ (0.01, 10) mm/s—values which are compatible with current state of the art HS-AFM devices [ 36 , 64 ]. In a corresponding fashion we bracket a range of diffusion constants relevant to the motion of lipids, proteins and protein complexes within a typical phospholipid cell membrane, sampling from D q ∈ [0.01,0.1,1] μm 2 s –1 .…”
Section: Theory and Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the simulations that follow, the scanned image area containing the mobile component is subjected to raster scanning at either a slow, medium or fast scanning speed such that t SCAN ∈ (1,10,100) s. Interpreted through the lens of Eqn. 5 this implies that for a square image scan area of L=10 μm, and a typical AFM device setup with a tip size ϕ ∈ (10, 100) nm, the required AFM cantilever tip oscillation frequencies and tip lateral scan velocities will be in the respective ranges, f ∈ (100, 1×10 6 ) and υ x ∈ (0.01, 10) mm/s—values which are compatible with current state of the art HS-AFM devices [ 36 , 64 ]. In a corresponding fashion we bracket a range of diffusion constants relevant to the motion of lipids, proteins and protein complexes within a typical phospholipid cell membrane, sampling from D q ∈ [0.01,0.1,1] μm 2 s –1 .…”
Section: Theory and Resultsmentioning
confidence: 92%
“…Non-penetrative measurements of a cell’s behavior principally involve the high spatial density recording of relatively soft interactions between the AFM tip and the outer cell membrane [ 28 , 29 ]. However, due to its non-equilibrium nature the cell membrane is a dynamic structure that changes over time [ 30 36 ]. In terms of how this change occurs, we make a distinction between (i) relatively large-scale (~100nm) gross morphological changes in membrane shape that occur slowly with a time constant, τ 1 (~minutes) [e.g.…”
Section: Theory and Resultsmentioning
confidence: 99%
“…Application of simulation AFM can reach much beyond just the interpretation of what is observed in an AFM image. We have previously shown that new structural models with atomistic resolution can be retrieved for higher oligomeric arrangements of the Annexin V protein seen under HS-AFM [ 20 ]. Simulation AFM was recently applied in a demonstration study of a membrane transporter protein, showing that based on topographic imaging of only one membrane side, the functionally coupled conformational state at the remote opposite site can be predicted [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The simulated scanning method computationally emulates scanning of the molecular structure to produce pseudo AFM images. It has been employed in several studies to interpret experimental AFM images of proteins [8,[17][18][19][20][21][22], and in molecular simulations of flexible fitting biomolecular structures to experimental images [23] or to deduce information on the AFM tip shape [24].…”
Section: Introductionmentioning
confidence: 99%
“…15 The simulated scanning method computationally emulates scanning of the molecular structure to produce pseudo AFM images. It has been employed in several studies to interpret experimental AFM images of proteins, 8,16,17 and in molecular simulations to perform flexible fitting of biomolecular structures to experimental images 18 or to deduce information on the AFM tip shape. 19 The strengths of the stand-alone BioAFMviewer software are its user-friendly versatile interface and rich functionality.…”
Section: Introductionmentioning
confidence: 99%